Hannah's war : a novel - Eliasberg, Jan (Little, Brown and Company, 2020)
"Berlin, 1938. Groundbreaking physicist Dr. Hannah Weiss is on the verge of the greatest discovery of the 20th century: splitting the atom. She understands that the energy released by her discovery can power entire cities or destroy them. Hannah believes the weapon's creation will secure an end to future wars, but as a Jewish woman living under the harsh rule of the Third Reich, her research is belittled, overlooked, and eventually stolen by her German colleagues. Faced with an impossible choice, Hannah must decide what she is willing to sacrifice in pursuit of science's greatest achievement. New Mexico, 1945. Returning wounded and battered from the liberation of Paris, Major Jack Delaney arrives in the New Mexican desert with a mission: to catch a spy. Someone in the top-secret nuclear lab at Los Alamos has been leaking encoded equations to Hitler's scientists. Chief among Jack's suspects is the brilliant and mysterious Hannah Weiss, an exiled physicist lending her talent to J. Robert Oppenheimer's mission. All signs point to Hannah as the traitor, but over three days of interrogation that separate her lies from the truth, Jack will realize they have more in common than either one bargained for"--